Lack of Proinflammatory Cytokine Interleukin-6 or Tumor Necrosis Factor Receptor-1 Results in a Failure of the Innate Immune Response after Bacterial Meningitis - Lea-Jessica Albrecht; Simone C. Tauber; Julika Merres; Eugenia Kress; Matthias B. Stope; Sandra Jansen; Thomas Pufe; Lars-Ove Brandenburg (Mediators of Inflammation)
The most frequent pathogen that causes bacterial meningitis is the Gram-positive bacterium Streptococcus pneumoniae. By entering the brain, host cells will be activated and proinflammatory cytokines like interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) are released. The goal of the current study was to examine the interaction between IL-6 and TNFR1 as receptor for TNF-α and the innate immune response in vivo in a model of Streptococcus pneumoniae-induced meningitis. For the experiments IL-6−/−, TNFR1−/−, and TNFR1-IL-6−/− KO mice were used. Our results revealed higher mortality rates and bacterial burden after infection in TNFR1−/−, IL-6−/−, and TNFR1-IL-6−/− mice and a decreased immune response including lower neutrophil infiltration in the meninges of TNFR1−/− and TNFR1-IL-6−/− mice in contrast to IL-6−/− and wild type mice. Furthermore, the increased mortality of TNFR1−/− and TNFR1-IL-6−/− mice correlated with decreased glial cell activation compared to IL-6−/− or wild type mice after pneumococcal meningitis. Altogether, the results show the importance of TNFR1 and IL-6 in the regulation of the innate immune response. The lack of TNFR1 and IL-6 results in higher mortality by weakened immune defence, whereas the lack of TNFR1 results in more severe impairment of the innate immune response than the lack of IL-6 alone.